2020
DOI: 10.1177/0886260520916268
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and Perpetration of Recent Intimate Partner Violence Among Women and Men Living in an Informal Settlement in Nairobi, Kenya: A Secondary Data Analysis

Abstract: Evidence suggests an overlap between intimate partner violence (IPV) experience and perpetration. However, few studies in sub-Saharan Africa have investigated experience and perpetration of IPV among women and men within the same community. This study reports prevalence of past-year IPV experience and perpetration among women and men living in an informal settlement in Nairobi, Kenya, and factors associated with IPV. Data analyzed for this study involved a geographically distributed random sample of 273 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
(58 reference statements)
5
8
0
1
Order By: Relevance
“…Our results do align with prior research among Kenyan adults [52] and youth in Tanzania [44] showing higher but similar levels of recent and lifetime IPV experiences and perpetration among women and men. High levels of both experiencing and perpetrating violence among men and women in heterosexual relationships has been previously reported among adults in Kenya, with a 2022 study showing that 23% of women and 18% of men experienced physical violence in their relationship in the 12 months prior to being interviewed [52]. The same study showed that IPV perpetration was higher among those also reporting experiencing IPV among both women and men [52].…”
Section: Discussionsupporting
confidence: 90%
“…Our results do align with prior research among Kenyan adults [52] and youth in Tanzania [44] showing higher but similar levels of recent and lifetime IPV experiences and perpetration among women and men. High levels of both experiencing and perpetrating violence among men and women in heterosexual relationships has been previously reported among adults in Kenya, with a 2022 study showing that 23% of women and 18% of men experienced physical violence in their relationship in the 12 months prior to being interviewed [52]. The same study showed that IPV perpetration was higher among those also reporting experiencing IPV among both women and men [52].…”
Section: Discussionsupporting
confidence: 90%
“…Finally, the same conditions that predispose individuals to violence in childhood could also lead to violence revictimization in adolescence and adulthood (e.g., witnessing violence, low social support, living with the perpetrator, economic, or food insecurity) (Carlson et al, 2020). Specifically, prior analyses have found higher social support to be a buffer against both childhood and intimate partner violence experiences while witnessing violence may be a marker of high rates of community violence and general acceptability of violent behavior (Machisa et al, 2018; Ringwald et al, 2020). We accounted for this by included family support and witnessing childhood violence as potential confounders of the relationship between childhood and IPV as other.…”
Section: Discussionmentioning
confidence: 99%
“…IPV gets marginal attention in global urban reports which tend to focus on insecurity, crime, and violence more broadly. However, IPV studies conducted among women ( Ringwald et al, 2020 ; Orindi et al, 2020 ; Swart, 2012 ) and men ( Ringwald et al, 2020 ) in informal settlements in Nairobi reported rates of IPV above KDHS urban prevalence estimates. Contrary to widely reported gender gaps, IPV studies in informal settlements in Nairobi and Dar-es-salaam found comparable rates among women and men ( Ringwald et al, 2020 ; Mulawa et al, 2018 ).…”
Section: Introductionmentioning
confidence: 92%
“…However, IPV studies conducted among women ( Ringwald et al, 2020 ; Orindi et al, 2020 ; Swart, 2012 ) and men ( Ringwald et al, 2020 ) in informal settlements in Nairobi reported rates of IPV above KDHS urban prevalence estimates. Contrary to widely reported gender gaps, IPV studies in informal settlements in Nairobi and Dar-es-salaam found comparable rates among women and men ( Ringwald et al, 2020 ; Mulawa et al, 2018 ). The impact of IPV in informal settlements may be particularly grave due to the economic burden of IPV-related harm on survivors, families, and communities ( National Gender and Equality Commission, 2016 ).…”
Section: Introductionmentioning
confidence: 92%